Jahresbericht 2020/2021 | Annual report 2020/2021 - Völker, Stephan; Schumacher, Heike (Universitätsverlag der Technischen Universität Berlin, 2022)
The annual reports of the Chair of Lighting Technology provide information on courses and current research projects and give an overview of the colleagues, their publications and committee activities.